A comparative study on sorption behavior of graphene oxide and reduced graphene oxide towards methylene blue. (December 2022) - Jahan, Nusrat; Roy, Hridoy; Reaz, Akter H.; Arshi, Shasawti; Rahman, Ehsanur; Firoz, Shakhawat H.; Islam, Md. Shahinoor
Abstract: Graphene oxide (GO) and reduced graphene oxide (rGO) were synthesized from graphite powder to compare the adsorption capacity of GO and rGO towards a cationic dye-methylene blue (MB). These synthesized nanomaterials were analyzed by Fourier Transform-Infrared Spectroscopy (FTIR), Brunauer-Emmett-Teller (BET), and Field Emission Scanning Electron Microscope (FESEM). FTIR results indicated the presence of larger number of oxygenated functional groups in the GO as compared to rGO surface suggests the conversion of GO to rGO. Scattered layers of graphite sheets with chunks of pores present in the GO surface were marked by FESEM. The effect of contact time and adsorbent dosage have been studied to make an efficient comparison between the adsorption capacity of GO and rGO for removing MB. GO showed an excellent adsorption capacity by removing 98.67% of MB dye within 4 h, while rGO could remove 93.47% of MB within 7 h from the aqueous solution. The maximum adsorption capacities of GO and rGO were 3333 mg/g and 2000 mg/g, respectively. The findings reveal the contribution of electrostatic interaction, H-bonds, and π–π interactions for the sorption of MB onto GO and rGO. The abundance of oxygen-containing functional groups substantially raised the sorption capacity of GO compared to rGO by at least 60%. The higher specific surface area of GO (9.10 m 2 /g) compared to rGO (0.60 m 2 /g) was another contributing factor to higher MB sorption. The sorption process was well described by a pseudo-second-order kinetics model, suggesting that the adsorption of MB by GO and rGO was mostly controlled by chemisorption. The Langmuir isotherm model fitted best (R 2 > 0.9) for both adsorbents indicating monolayer sorption on a uniform surface with a finite number of adsorption sites. These results suggest that GO can be preferred over rGO for removing cationic pollutants from wastewater. Graphical abstract: Image 1 Highlights: GO surface has a larger number of O-containing functional groups than rGO. Flake-like, thick sheet porous structure and wrinkled edge shaped GO was formed. Higher surface area of GO (9.10 m 2 /g) compared to rGO (0.60 m 2 /g) was observed. GO removed 98.67% of Methylene blue dye within 4 h against 93.47% removal by rGO within 7 h. Isotherms and kinetics for GO and rGO followed Langmuir and pseudo-2nd order models, respectively.